2009
DOI: 10.1021/ar8001816
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Ion Recognition by Chelating and Cationic Boranes

Abstract: Because of the ubiquity of fluoride ions and their potential toxicity at high doses, researchers would like to design receptors that selectively detect this anion. Fluoride is found in drinking water, toothpaste, and osteoporosis drugs. In addition, fluoride ions also can be detected as an indicator of uranium enrichment (via hydrolysis of UF(6)) or of the chemical warfare agent sarin, which releases the ion upon hydrolysis. However, because of its high hydration enthalpy, the fluoride anion is one of the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
285
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(292 citation statements)
references
References 62 publications
3
285
0
4
Order By: Relevance
“…F -binding with the boron atom leads to a modulation of the electronic properties of the chromophore resulting in changes in colour and/or fluorescence emission. 123 In these studies it was observed that the introduction of cationic boranes favours the binding of F -in aqueous solutions due to the presence of coulombic attractive interactions. anions.…”
mentioning
confidence: 99%
“…F -binding with the boron atom leads to a modulation of the electronic properties of the chromophore resulting in changes in colour and/or fluorescence emission. 123 In these studies it was observed that the introduction of cationic boranes favours the binding of F -in aqueous solutions due to the presence of coulombic attractive interactions. anions.…”
mentioning
confidence: 99%
“…Cationic borane is known as a potent chelator for fluoride [3]. It is now important to explore the therapeutic role of boranes and antioxidant catechin hydrate either alone or in combination; delivered through nanocapsule to treat fluoride induced oxidative damage in rats.…”
Section: Resultsmentioning
confidence: 99%
“…Cationic boranes form chelate complexes with fluoride anions [3]. Catechin hydrate, a polyphenolic flavonol antioxidant exhibits its properties against many diseases including ischemic neurodegeneration, atherosclerosis, stomach cancer etc.…”
Section: Introductionmentioning
confidence: 99%
“…NMR spectra were recorded in C 6 [10] and LiC 6 H 2 (2,4,6-i-Pr) 3 [63] were obtained according to literature procedures. Commercially available LiCl (anhydrous), LiBr (anhydrous), KClO 4 and H 2 N(i-Pr) were used without further purification.…”
Section: Methodsmentioning
confidence: 99%